(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
This study aims to determine the meaning of movement in the Lopi Penge dance in Bima. This type of research is descriptive qualitative, qualitative data technique used is data trigulation which includes observation, interviews and literature study. The main problems in this study consist of 2 (two) first, what is the form and meaning of the Lopi Penge song as an accompaniment in the Lopi Penge dance in Bima and the second, what are the forms and meanings contained in the Lopi Penge dance in Bima. The results showed that the Lopi Penge dance is a dance that has a very deep historical meaning and value for the Bima people, the Lopi Penge dance is usually danced during the harvest season, weddings, and other major events in Bima. In addition, the Lopi Penge dance also serves to unite and foster a sense of belonging and love between the Bima people.